Influence of Wiring Connection Mode on Grounding Potential Ｒise in Voltage Transient Circuits - ZHAO Miao (Journal of Harbin University of Science and Technology, 2021)
Ground potential fluctuation caused interferences or even irreversible damage to the control and measurement circuit in the voltage transient system. To study the influence law of wiring on ground potential，two typical wirings were analyzed in the simplest voltage transient circuit. The parameters of each component in the circuit were estimated and simulated to obtain the voltage waveforms of the common ground point in the voltage transient circuit with two wirings. The test circuit was built to measure the voltage waveforms of the common ground point in the voltage transient circuit. The results showed that the voltage drop which was formed by the charging current of the distributed capacitance flowing through the ground impedance during a voltage transient was the basic reason for the ground potential floating; the switch positions were different and the capacitances charged during the voltage transient was different，therefore the floating of the ground potential was different; the floating amplitude of ground potential in voltage transient circuits could be reduced by arranging high voltage switches rationally.